The boundaries of liberty and tolerance : the struggle against Kahanism in Israel - Cohen-Almagor, Raphael (University Press of Florida, 1994)
In 1985, Raphael Cohen-Almagor participated in an Israeli demonstration against Rabbi Meir Kahane, a religious, quasi-fascist propagandist who had been elected to the Israeli parliament the preceding year. As the demonstration became a confrontation - people screamed, shouted, and whistled to prevent Kahane from speaking - Cohen-Almagor felt increasing discomfort. In the name of democracy, the protesters were using the same tactics against Kahane that Kahane would use against his own opposition. Advocates of free speech were denying Kahane free speech. The paradox was the impetus behind this work, which proposes to overcome what Cohen-Almagor calls the "catch" of democracy, the idea that the principles that underlie any political system might also bring about its destruction. Building on the framework of John Stuart Mill and other liberal theorists, Cohen-Almagor addresses the delicate issue of which boundaries should be set to safeguard democracy. He contends that restrictions of liberty and tolerance may be prescribed when there are threats of immediate violence against individuals or groups, or when the intent of a threat is to inflict psychological damage in circumstances when the target group is forced to be exposed to the threat. In this connection he reviews the ruling of the Illinois Supreme Court that permitted American Nazis to hold a demonstration in Skokie, and he argues that the decision was wrong. The second part of the book explores the struggle of the Israeli political system against the Kahanist racist phenomenon as it has developed in the last two decades. Cohen-Almagor's perspective differs from that of philosophers who focus particularly on practical considerations. "My view is that the fundamental question is ethical rather than practical," he writes. "I argue that, as a matter of moral principle, violent parties that act to destroy democracy or the state should not be allowed to run for parliament." This work, both a theoretical contribution and a discussion of a major current political problem, will be valuable to political scientists, philosophers, legal scholars, and anyone interested in First Amendment issues